2014
DOI: 10.4317/medoral.20205
|View full text |Cite
|
Sign up to set email alerts
|

Oral potentially malignant disorders: Is malignant transformation predictable and preventable?

Abstract: Leukoplakia is the most common potentially malignant disorder of the oral mucosa. The prevalence is approximately 1% while the annual malignant transformation ranges from 2% to 3%. At present, there are no reliable clinicopathological or molecular predicting factors of malignant transformation that can be used in an individual patient and such event can not truly be prevented. Furthermore, follow-up programs are of questionable value in this respect. Cessation of smoking habits may result in regression or even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(93 citation statements)
references
References 31 publications
2
86
1
4
Order By: Relevance
“…Potentially malignant lesions in the oral mucosa are commonly defined, on an histological basis, as oral dysplasia 1,2 and are associated with high rates of progression toward oral squamous cell carcinoma (OSCC). 3,4 Despite the relevance of these lesions, the rates of progression from oral dysplasia toward invasive cancer remain disparate, which is due, in part to the complexity of histopathological diagnosis, and, because no specific markers are available for assuring the evolution of oral dysplasia.…”
Section: Introductionmentioning
confidence: 99%
“…Potentially malignant lesions in the oral mucosa are commonly defined, on an histological basis, as oral dysplasia 1,2 and are associated with high rates of progression toward oral squamous cell carcinoma (OSCC). 3,4 Despite the relevance of these lesions, the rates of progression from oral dysplasia toward invasive cancer remain disparate, which is due, in part to the complexity of histopathological diagnosis, and, because no specific markers are available for assuring the evolution of oral dysplasia.…”
Section: Introductionmentioning
confidence: 99%
“…The rate of malignant development reported in various studies ranges from 0.13% to 50% depending on the subtype distribution, the number of cohorts, and the corresponding treatment types. 24,25 A follow-up study of 218 patients who did not receive surgical intervention indicated that the leukoplakia localized on the tongue, had a higher degree of dysplasia, or were nonhomogeneous in appearance, with a significant risk of progression to cancer. 14 Oral leukoplakia, as the most common OPMD, is defined as a predominantly white lesion of the oral mucosa that cannot be characterized as any other definable type.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] Actinomyces, Streptococcus and Capnocytophaga are also reported to be minimally affected by metronidazole. 6 Chronic periodontitis is caused by a mixed microbial infection making the selection of targeted antibiotic difficult to justify.…”
Section: Antibiotics Protocolmentioning
confidence: 99%
“…4 Patients should be carefully reviewed for such events. OLP management must also encompass its malignant potential and oral cancer development which may be in up to 3.5% of cases 5,6 with essential long-term monitoring of patients to identify and diagnose early dysplastic and malignant changes. 7 Any patient with possible OLP should be initially referred to specialists to ensure that the diagnosis is formally confirmed, appropriate treatment is provided and adequate, evidence-based information is given.…”
Section: Oral Medicine Off-label Cream Usementioning
confidence: 99%